Audit Quality, Board Governance and Real Earnings Management – Indonesian Evidence - KRISMIAJI; HANDAYANI; SUMAYYAH (CECCAR Business Review, 2023)

(untitled)
This paper outlines the research that investigates the impact of audit quality on earnings management with board governance moderation. Audit quality is proxied by audit firm size, while board governance is measured by board independence. This research used data on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 and obtained 102 companies or 510 firm-year observances. This research found that a strong governance board encourages the quality of auditors to prevent real earnings management practices. When real earnings management is decomposed into three measures, the measure that produces the findings is consistent with aggregate real earnings management, only real management of production costs. Meanwhile, real earnings management of operating cash flows produces insignificant findings, while real management of discretionary expenditures produces opposite results. This research complements the previous literature on earnings management and the variables that influence it, both positive and negative influences.